Phase 2 Trial of Rituximab in Acetylcholine Receptor Antibody-Positive Generalized Myasthenia Gravis: The BeatMG Study. (25th January 2022) - Nowak, Richard J.; Coffey, Christopher S.; Goldstein, Jonathan M.; Dimachkie, Mazen M.; Benatar, Michael; Kissel, John T.; Wolfe, Gil I.; Burns, Ted M.; Freimer, Miriam L.; Nations, Sharon; Granit, Volkan; Smith, A. Gordon; et al.
Abstract : Background and Objective: To determine whether rituximab is safe and potentially beneficial, warranting further investigation in an efficacy trial for acetylcholine receptor antibody-positive generalized myasthenia gravis (AChR-Ab+ gMG). Methods: The B-Cell Targeted Treatment in MG (BeatMG) study was a randomized, double-blind, placebo-controlled, multicenter phase 2 trial that utilized a futility design. Individuals 21–90 years of age, with AChR-Ab+ gMG (MG Foundation of America Class II–IV) and receiving prednisone ≥15 mg/d were eligible. The primary outcome was a measure of steroid-sparing effect, defined as the proportion achieving ≥75% reduction in mean daily prednisone dose in the 4-weeks prior to week 52 and with clinical improvement or no significant worsening as compared to the 4-week period prior to randomization. The coprimary outcome was safety. Secondary outcomes included MG-specific clinical assessments. Fifty-two individuals were randomized (1:1) to a 2-cycle rituximab/placebo regimen, with follow-up through 52 weeks. Results: Of the 52 participants included, mean ± SD age at enrollment was 55.1 ± 17.1 years; 23 (44.2%) were women and 31 (59.6%) were Myasthenia Gravis Foundation of America Class II. The mean ± SD baseline prednisone dose was 22.1 ± 9.7 mg/d. The primary steroid-sparing outcome was achieved in 60% of those on rituximab vs 56% on placebo. The study reached its futility endpoint ( p = 0.03), suggesting that the predefined clinically meaningful improvement of 30% due to rituximab over placebo was unlikely to be achieved in a subsequent, larger trial. No safety issues were identified. Discussion: Although rituximab was safe and well-tolerated, these results suggest that there is a low probability of observing the defined clinically meaningful steroid-sparing effect over a 12-month period in a phase 3 trial of mild to moderately symptomatic AChR-Ab+ gMG. Classification of Evidence: This study provides Class I evidence that for mild to moderate AChR-Ab+ gMG, compared with placebo, rituximab is safe but unlikely to reduce steroid use by an absolute difference of at least 30% at 1 year. Trial Registration Information: ClinicalTrials.gov identifier: NCT02110706.